The Effect of Hip and Ankle Joint Abductor/Adductors Fatigue on Dynamic Balance of Soccer Players - Kamran Johari; Seyed Sadredin Shojaedin (Sport Sciences and Health Research)
The aim of this study was to examine the effect of hip and ankle jointabductor/adductors fatigue on the dynamic balance of soccer players. 20male physical education students (Mean±SD, age: 20.24±0.73 yrs, height:170.27±4.28 cm, weight: 67.38±7.24 kg, and BMI: 23.22±2.02 kg/m²) whoparticipated three times per week in university soccer team program,without any lower extremity injury voluntarily participated in this study. Inorder to estimate the participants' dynamic balance, Star Excursion BalanceTest (SEBT) in eight directions was applied after a short warm-up.Dynamometer Isokinetic Biodex was used to execute fatigue in hip andankle joint abductor/adductor muscles. Each subject participated in twomuscle fatigue sessions. In each session, the fatigue program was randomlyassigned to one of the muscle groups of hip abductor/adductor and anklejoint evertor/inventor in repeated contractions until reaching 50% ofprimary maximum torque with the interval of 72 hours in the same situationas far as possible. Afterwards, SEBT posttest was conducted. Descriptivestatistics, dependent t test and variance analysis (with repeated measures)was used for statistical analysis at P<0.05. The isokinetic fatigue of hip andankle joint abductor/adductors significantly decreased the accessibledistance in SEBT test. Furthermore, fatigue program in the hipabductor/adductors decreased the accessible distance more than the anklejoint evertor/inventors. Due to the results, the fatigue of hipabductor/adductors was more effective in the dynamic balance of soccerplayers than ankle joint evertor/inventors.